In vitro antibacterial efficacy of leucas cephalotes (roth) spreng. (lamiaceae) against some gram positive and gram negative human pathogens - Khan, Abdul Viqar; Ahmed, Qamar Uddin; Khan, Athar Ali; Shukla, Indu (Science Target, 2014)
Leucas cephalotes (Roth.) Spreng (family: Lamiaceae) is a rainy season weed widely distributed in tropical regions of Asia at elevation up to 1,700 m, medicinally employed for the treatment of skin diseases, fever, hepatic disorders, urinary complaints cough and cold. The traditional uses of this plant strongly suggest its possible antibacterial properties, but its efficacy has not been examined in broad scenes, in present communication, its antibacterial efficacy has been explored. Polar and non-polar extracts (ethyl acetate, methanol, aqueous, benzene, and petroleum ether) at five different concentrations (0.5, 1, 2, 5, and 10 mg/mL) were evaluated for their antibacterial efficacy against seven G+ and eleven G– hospital isolated bacteria. Disc diffusion method was followed to determine antibacterial activity. Phytochemical analysis of plant revealed presence of tannins, glycosides, saponins, steroids, phenolic compounds and flavonoids as secondary metabolites. Maximum antibacterial activity was demonstrated by ethyl acetate and methanol extracts at a minimum concentration (0.5 mg/mL/disc). Extracts were effective on both types of test pathogens. From the present findings, it may be concluded that the plant could be formulated in broad spectrum antibiotic and confirms the traditional uses in pathogenic diseases. Keywords: Leucas cephalotes (Roth) Spreng, Antibacterial efficacy, crude extracts, traditional uses